The Evolving Portrayal of Female Emotions in the Marvel Cinematic Universe. Issue 1 (3rd April 2022) - Jones, Benjamin
ABSTRACT: Historically, female characters in comic books have largely been assigned to supporting roles, dressed to cater to the male gaze, or sometimes disregarded as mere plot devices to advance the stories of male characters. In more recent years, this has started to change with a select number of female characters' stories being highlighted by major blockbuster releases. This article will explore the way that female representation has evolved in the Marvel Cinematic Universe over the past decade, with special focus on three key scenes in Marvel's The Avengers, Captain Marvel, and WandaVision that reflect an evolution in the way that female emotions are handled within the narrative of these franchises. Discussion will be given to the way these pop culture messages influence the work that feminist therapists do with clients from a narrative perspective.